Comparison of Euler and trapezoidal approaches for capacitor switching transient - T. Thanasaksiri (2018)
© 2017 IEEE. This paper compares the capacitor voltage by numerical simulation using the Euler integration technique, the trapezoidal rule (the same format used by EMTP) and also the simulation using the EMTP-ATPDraw program. A 115/22 kV transformer supplies a resistive load which is connected in parallel with the switchable capacitor bank has been modeled. The capacitor voltage from EMTP approach is exactly match with the voltage from EMTP-ATPDraw program. The inductor current can also be found if required and the inductor current from EMTP approach is exactly match with the current from EMTP-ATPDraw program as well.